THE EFFECTIVENESS OF PHYSICAL AND ALKALI HYDROTHERMAL PRETREATMENT IN IMPROVING ENZYME SUSCEPTIBILITY OF SWEET SORGHUM BAGASSE (Jurnal Bahan Alam Terbarukan, 2017)
Sweet sorghum bagasse (SSB) obtained after juice extraction is a potential feedstock for fermentable sugars production that can be further fermented to different kinds of products, such as ethanol or lactic acid. The proper particle size resulted from phsyical pretreatment and different pretreatment processes including water, alkali, hydrothermal, and alkali hydrothermal for improving enzyme susceptibility of SSB have been investigated. After grinding to particle sizes of 250 μm, 250-420 μm, and, 420 μm the sweet sorghum bagasse was washed to eliminate residual soluble sugars present in the bagasse. Dosages of cellulase enzyme used in saccharification were 60 and 100 FPU/g substrate, respectively. The results showed that SSB with particle sizes of 250-420 μm had the highest cellulose (38.33%) and hemicellulose content (31.80%). Although the yield of reducing sugar of 250-420 μm size particles was lower than that of smaller particle (250 μm), the former was more economical in the energy consumption for milling process. The yields of reducing sugar obtained from enzymatic hydrolysis of alkali hydrothermal pretreated sweet sorghum bagasse were 1.5 and 0.5 times higher than that from untreated sweet sorghum bagasse at enzyme loading of 100 and 60 FPU/g substrate, respectively. Furthermore, alkali hydrothermal pretreatment was able to remove as much as 85% of lignin. Morphological analysis using SEM (Scanning Electron Microscope) showed that samples treated with alkali hydrothermal have more pores and distorted bundles than that of untreated sweet sorghum bagasse. Meanwhile, XRD (X-ray diffraction) analysis showed that pretreated samples had a higher crystallinity and smaller crystallite size than untreated sweet sorghum bagasse, which might be due to removal of amorphous lignin components.